Segregation and inequality in Chicago Public Schools, transformed and intensified under corporate education reform - Pavlyn Jankov; Carol Caref (Arizona State University, 2017)
During the period of 1981 to 2015, the total population of Black students in CPS plummeted from close to 240,000, 60% of all CPS students, to 156,000 or 39% of CPS. This paper documents how despite their decreasing numbers and percentage in the system, the vast majority of Black students remained isolated in predominantly low-income Black schools that also became the target of destabilizing corporate reforms and experimentation. This study examines the historic and contemporary dual segregation of Black teachers and Black students in Chicago Public Schools, and how mass school closures, privatization, and corporate school reform have both transformed and deepened segregation and resource-inequity across Chicago's schools.